2011
DOI: 10.1074/jbc.m111.270454
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fertility, Survival, and Cuticle Collagen Function by the Caenorhabditis elegans eaf-1 and ell-1 Genes

Abstract: EAF2, an androgen-regulated protein, interacts with members of the ELL (eleven-nineteen lysine-rich leukemia) transcription factor family and also acts as a tumor suppressor. Although these proteins control transcriptional elongation and perhaps modulate the effects of other transcription factors, the mechanisms of their actions remain largely unknown. To gain new insights into the biology of the EAF2 and ELL family proteins, we used Caenorhabditis elegans as a model to explore the in vivo roles of their worm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…ALF50 ( eaf-1(tm3976) ) was described previously [1]. ZH231 unc-76 ( e911 ) V ; enIs7 [ Pced-1 ced-1 :: GFP + unc-76 (+)] X [9] was generously provided by Zheng Zhou (Baylor College of Medicine, Houston, TX).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALF50 ( eaf-1(tm3976) ) was described previously [1]. ZH231 unc-76 ( e911 ) V ; enIs7 [ Pced-1 ced-1 :: GFP + unc-76 (+)] X [9] was generously provided by Zheng Zhou (Baylor College of Medicine, Houston, TX).…”
Section: Methodsmentioning
confidence: 99%
“…The EAF-1 protein forms a protein complex with the ELL ortholog ELL-1, and together these proteins control fertility, body size, and the expression of cuticle collagens in worms [1]. Despite these important functions, genetic deletion of the eaf-1 gene in the worm is not lethal but leads to a reduction in fertility, where eaf-1 mutants produce ~150 offspring instead of the normal 300.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Simone et al, showed that endogenous EAF2 coimmunoprecipitated with transfected ELL2 in 293 cells and that like the MLL-ELL fusion protein (Lavau, et al 2000), MLL-EAF2 could immortalize hematopoietic progenitor cells in vitro. Recently, eaf-1 and ell-1, worm orthologs of EAF1 , EAF2 and ELL1 and ELL2 , were shown to have overlapping function in the regulation of fertility, survival and cuticle formation in C. elegans (Cai, et al 2011). In advanced prostate cancer, EAF2 protein was down-regulated (Xiao, et al 2003; Ai, et al 2013; Pascal, et al 2013); and, overexpression of EAF2 in prostate cancer cell lines induced apoptosis and inhibited the growth of xenograft tumors (Xiao et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While C. elegans does contain homologs for a subset of the SEC components, specifically ELL1 (Y24D9A.1), AFF9 (Y55B1BR.1 and Y55B1BR.2), and EAF (D1007.16), these factors do not appear to play an essential role in transcription. 157 Furthermore, knock down of ELL and AFF9 does not significantly affect either Ser2-P levels or viability (E.A. Bowman, W.G.…”
Section: Elegans Somatic Ser2-p Requires Cdk-9 and Cdk-12mentioning
confidence: 99%